Field of View Issues on the Flight Deck: Meta-Analyses to Examine the Effects of Eccentricity, Salience, and Expectancy on Detection and Discrimination. (September 2016) - Wickens, Christopher; Sebok, Angelia; McCormick, Patricia; Walters, Brett
Twenty-eight empirical studies provided data for four meta-analyses on visual detection and discrimination inflight-decktypical tasks, at varying degrees of eccentricity relative to a central point of interest. The data revealed a general trend for poorer performance at increasing eccentricity, and greater degradation when eye movements were prevented. The data failed to reveal a systematic discontinuity of performance degradation beyond 15°, which defines the typical "primary field of view" in the cockpit, but they reveal a 14% miss rate and 21% discrimination error rate at that location. The results also point to the profound influence of moderator variables of expectancy and salience on eccentric visual performance.